Analysis on reoperations and impact on the pancreas transplantation results - Genzini, Tercio; Crescentini, Fabio; Carneiro, Arie; Rangel, Erika Bevilaqua; Antunes, Irina; Sakuma, Hebert; Scomparin, Patrick Salomão; Ferreira, Felipe Yamauti; Miranda, Marcelo Perosa de (Brazilian Journal of Transplantation, 2009)
Many factors which include advancements in the surgery techniques and immunosuppression have been brought significant improvement on the results of the graft and patient survival submitted to pancreatic transplants. However, a third part of these patients is submitted to reoperations (ReOps). Purposes: To assess the distribution of ReOps among the PT categories in the post-operatory period (premature or late) and to analyze the impact of these operations on the patient and graft survival. Methods: Unicentric, retrospective study carried out through the data collection from charts of 182 patients submitted to PT from January of 2000 until December of 2007. Results: 88 reoperations were performed in 73 patients, being 43 premature operations, and 41 late operations. PTRS group presented higher incidence of premature ReOps related to other groups. The group submitted to premature ReOp presented lower survival rate (87.2%) when compared to the non-operated group, and a similar survival rate (97.5%) when compared to the group submitted to late ReOp. Related to the pancreatic grafting survival after one year, it was verified that the premature ReOp group had a lower survival rate compared to the late ReOp group, both presenting significantly worse results then the group with no ReOp. Conclusion: Post-PT ReOps has a direct relationship towards a successful procedure. When performed in the first 3 months after PT, they determined a negative impact on the survival of patient and graft.